2008
DOI: 10.1063/1.2832760
|View full text |Cite
|
Sign up to set email alerts
|

Patterned epitaxial vapor-liquid-solid growth of silicon nanowires on Si(111) using silane

Abstract: We have carried out a detailed study on the vapour-liquid-solid growth of silicon nanowires (SiNWs) on (111)-oriented Si substrates using Au as catalytic seed material. Arrays of individual seeds were patterned by electron-beam lithography, followed by Au evaporation and lift-off. SiNWs were grown using diluted silane as precursor gas in a low-pressure chemical vapor deposition system. The silane partial pressure, substrate temperature, and seed diameter were systematically varied to obtain the growth rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
124
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(136 citation statements)
references
References 17 publications
12
124
0
Order By: Relevance
“…Lew et al 12 investigated nanowire growth at a similar temperature range and reported an activation energy of 22 kcal/mol. However, their data seem to indicate a somewhat smaller value, closer to the 19 kcal/mol of Schmid et al 29 From the data of Bootsma and Gassen, 30 who studied Si nanowires growth at temperatures of 600-800°C, an activation energy of 11.1 ( 0.4 kcal/mol (0.48 ( 0.02 eV) can be deduced.…”
Section: Low Temperature Chemical Vapor Depositionmentioning
confidence: 93%
See 4 more Smart Citations
“…Lew et al 12 investigated nanowire growth at a similar temperature range and reported an activation energy of 22 kcal/mol. However, their data seem to indicate a somewhat smaller value, closer to the 19 kcal/mol of Schmid et al 29 From the data of Bootsma and Gassen, 30 who studied Si nanowires growth at temperatures of 600-800°C, an activation energy of 11.1 ( 0.4 kcal/mol (0.48 ( 0.02 eV) can be deduced.…”
Section: Low Temperature Chemical Vapor Depositionmentioning
confidence: 93%
“…Si nanowires obtained by using Au and silane are usually only slightly tapered, which indicates that radial growth is slow compared to axial growth. According to the data by Schmid et al, 29 radial growth rates are about 2 orders of magnitude smaller than axial growth rates. The activation energy for radial growth is found to be larger than that for axial growth.…”
Section: Low Temperature Chemical Vapor Depositionmentioning
confidence: 99%
See 3 more Smart Citations